Cloud Security Issues, Techniques and Concerns – An Overview - Negi, V (International Journal of Computer Sciences and Engineering, 2019)
Among cloud computing resources like networks, servers, storage, applications and services, Storage is one of the major resource that is being used at large by the cloud users. Small to mid-sized business houses use Storage-as-a-Service to enhance business availability and reliability, managing backups and to extenuate risks involved in disaster recovery. Security, therefore, becomes the most critical aspect due to the confidential and intimate information being stored on the public cloud. In public cloud, since the services are being provided by the third party service providers, which are geographically dispersed and involve resources outside the user’s premises, the three service models (IaaS, PaaS, SaaS) face serious security threats. Public cloud can fall prey to threats like Data breaches, insufficient identity, insecure APIs, system vulnerabilities, account hijacking, malicious insiders, data loss, insufficient due diligence, DoS and abuse of cloud services. This paper presents a review on the most pressing security issues within cloud computing, the techniques that can be employed in addressing such cloud security issues and the challenges.